Gender transformative approaches in value chain development: Challenging norms and roles - Kruijssen, Froukje (International Livestock Research Institute, 2016)
The research team tried to integrate gender-transformative approaches in analysing the fish value chain. It developed tools that can be used alone or integrated in a conventional value-chain assessment. The idea was to understand the underlying causes for inequalities between men and women and factors supporting or hindering participation in the chain. The researchers looked at processes in decision making, roles and responsibilities, relationships and power dynamics, and gender norms. They did this using drawings and other interactive tools engaging with men, women and leaders. The tools make it possible to assess relations within the household, the community and the value chain. The tools were tested and integrated into a standard value-chain analysis. The results show that many gender norms inhibit women’s participation and benefits from value-chain activities. Interview with Froukje Kruijssen (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684